THE DELI MALAY TRIBE CULTURAL CENTER WITH NEO-VERNACULAR ARCHITECTURAL APPROACH - Andalucia, Andalucia; Shafwani , Shayra Anastasya (Komunitas Menulis dan Meneliti (Kolibi), 2024)
The Deli Malay ethnic group is the indigenous community of Medan City. However, after the Dutch colonial administration brought in Javanese and Chinese ethnic groups to Medan, the Deli Malay people, being in the minority, gradually decreased in number as other ethnic groups arrived in the city over the years. This situation, coupled with a lack of information and education about the culture of the Deli Malay people among the public, can lead to the neglect and marginalization of Deli Malay culture. This issue is concerning given the significant role that the Deli Malay people have played in the development of Medan since pre-colonialism times. To address this concern, the design of a Deli Malay Cultural Center is proposed. It aims to serve as an educational hub providing informative insights into the culture of the Deli Malay people to the general public. Additionally, it serves as a facility for the preservation of Deli Malay culture, incorporating a Vernacular Architecture approach. This is expected to blend Deli Malay cultural elements with modern features. This approach could be seen as a solution to promote and preserve Deli Malay culture. This design is also expected to be a symbol of cultural preservation and can inspire other community groups to continue to preserve their culture so that the diversity of tribes and cultures in Indonesia does not decrease or even become extinct. The research for this proposal is conducted using observational methods, literature studies, and precedents.